Ecologically sustainable human exploitation of the Gran Dolina TD10.2 bison (Sierra de Atapuerca, Spain) - Guillermo Rodríguez-Gómez; Antonio Rodríguez-Hidalgo; Palmira Saladié; Jan van der Made; Juan Marín; Andreu Ollé; Marina Mosquera; José María Bermúdez de Castro; Juan Luis Arsuaga; Eudald Carbonell (Scientific Reports)
Abstract There is evidence that communal hunting of bison was a practice that occurred from the Middle Pleistocene to historic times and was also observed among Indigenous Americans. Within the subsistence strategies of Pleistocene humans, communal hunting was part of their range of behaviors. The level TD10.2-BB of the Gran Dolina in the Sierra de Atapuerca preserves a fossil record of this practice, with remains of at least 60 bison of different age classes. This study aims to evaluate the hypothesis that human exploitation of these bison was sustainable. To this end, we analyzed the mortality pattern of bison from TD10.2-BB through dental remains using ternary diagrams and life tables. We also used allometric equations to estimate the mean body mass of the bison population and the potential energy yield they could have provided. Our results suggest a catastrophic mortality profile for the TD10.2-BB bison, with individuals of all age classes and no selective bias toward specific age classes. The life table derived from this profile suggests a growing bison population, indicating that human exploitation could have been sustained without causing a population collapse. Furthermore, our results suggest that bison would provide meat and energy resources to support large groups of humans for several days. While the high protein content of bison carcasses may have limited their full utilization, the availability of other resources in the ecosystem likely facilitated the optimal use of bison.